Evaluation of the pharyngeal airway dimensions measured by cephalometrics and cone beam computed tomography in patients with skeletal class II malocclusions - Trinh Thi Ngoc Nguyen; Lam Nguyen Le; Ngan Thi Bich Truong; Phung Thi Thanh Nguyen; Cuong Manh Tran; Tranh Thi Huyen Trinh; Loc Truong Tan; Kha Van Nguyen (Journal of Orthodontic Science, 2025)
OBJECTIVE: To assess the correlation between pharyngeal airway dimension measurements via cephalometrics and those via cone beam computed tomography (CBCT) in patients with skeletal Class II malocclusions. SUBJECTS AND METHODS: In this cross-sectional retrospective study, we reviewed the medical records of 106 patients referred for both CBCT and cephalometric imaging between 2022 and 2023 at Can Tho University of Medicine and Pharmacy Hospital. Pharyngeal airway dimensions were measured using WEBCEPH software for cephalometric analysis and Mimics Research software for CBCT image processing and analysis. RESULTS: A strong correlation between cephalometric films and CBCT images was observed regarding airway parameters. The airway volume exhibited a negative correlation with the ANB and SN-GoGn angles and a positive correlation with the SNB angle. CONCLUSIONS: Cephalometric analysis may serve as a fundamental screening tool to provide valuable information regarding the morphological characteristics of the airway as an alternative to CBCT.